Recent advancement in prodrugs - Shah, Kamal; Chauhan, Durgesh Nandini; Chauhan, Nagendra Singh; Mishra, Pradeep (Boca Raton, FL : CRC Press, 2020)
Recent Advancement in Prodrugs Drugs used as medicines have many limitations like low chemical stability, aqueous solubility, or oral absorption/bioavailability, rapid presystemic metabolism, toxicity, inadequate site specificity, or poor patient acceptance/compliance (unwanted adverse effects, unacceptable taste or odor, irritation or pain). Prodrugs design is an approach to overcome these limitations. Key features Covers recent advancements in development of prodrugs Presents balanced synthesis and applications of prodrug chemistry Discusses broad spectrum of prodrug categories and outlines industrial applications Reviews prodrugs in cancer nanomedicine, its therapy and treatment Elucidates mathematical models to study the kinetics of prodrugs This book covers recent advances in the design of prodrugs. It contains all the significant recent examples of prodrug chemistry developments and will aid academics and researchers seeking to generate new projects in the field.
OCLC-licensed vendor bibliographic record.
Keywords: Prodrugs; SCIENCE / Chemistry / Clinical